Pengaruh Integrated Marketing Communication terhadap Brand Image pada Auliacorp - Wirakanda, Gugum Gumilang; Shafa Annisa Arie (Universitas Haji Sumatera Utara, 2024)
This study aims to determine and evaluate Integrated Marketing Communicationsat Auliacorp, to determine and evaluate Brand Image at Auliacorp and to determinethe Influence of Integrated Marketing Communications on Brand Image atAuliacorp. With a descriptive quantitative approach method, the data analysistechnique uses simple linear regression. This study is a population study with asample and population of 30 respondents.The results of this study indicate that Integrated Marketing Communications has apositive and significant effect on Brand Image at Auliacorp by 84.2%